Les références célestes dans les coplas flamencas : sentimentalité, spiritualité et fatalisme - Vinciane Trancart (Etudes Epistémè)
In the flamenco songs, the cosmic terminology is very abundant, even though it is not particularly varied, the astral references (to the sun, the moon, the stars, etc.) are numerous and frequent. They are not mentioned for themselves, for a scientific purpose, but are an opportunity to refer to three fields in particular. First, that of feelings: the universe is mentioned to deal with love, attachment, affection or, on the contrary, hate towards another human being. The second field is that of belief, because through this cosmic lexicon, the lyrical self moves towards the afterlife: the sky is then evoked or invoked as a privileged place of transcendence. Flamenco religiosity is "cosmic" in the sense that the uses of this lexical field reveal the mixed influences of several inspirations: Jewish, Christian, Muslim, pagan... Ultimately, however, the sidereal terminology brings us back to the earth, insofar as it shows the relevance of fatality and fatalism in this Gypsy-Andalusian repertoire. Is it not the case that celestial references serve less to project oneself into infinity than to express, implicitly, a tragic human reality? Cathartically, the singing self, in the grip of everyday troubles, complains to the stars of his inevitable fate.